2005
DOI: 10.17705/1cais.01529
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Human-Computer Interaction Development into the Systems Development Life Cycle: A Methodology

Abstract: Incorporating a human computer interaction (HCI) perspective into the systems development life cycle (SDLC) is necessary to information systems (IS) success and, in turn, to the success of businesses. However, modern SDLC models are based more on organizational needs than human needs. The human interaction aspect of an information system is usually considered far too little (only the screen interface) and far too late in the IS development process (only at the design stage). Thus, often a gap exists between sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
0
52
0
1
Order By: Relevance
“…UCD [22], UE [20] and PD [21] are usability methods that focus on user involvement in software development process. The importance of HCI, which emphasize on human-centeredness, usability, human factors, user experience, design issues, as well as concerns on the success of businesses, management, and also organizations, has been accepted to some extent by practitioners [2]. Since user interacts with information, technology and task from various contexts [2], each design of software development must consider user involvement to ensure user satisfaction of the product.…”
Section: A User Involvement and Hcimentioning
confidence: 99%
See 3 more Smart Citations
“…UCD [22], UE [20] and PD [21] are usability methods that focus on user involvement in software development process. The importance of HCI, which emphasize on human-centeredness, usability, human factors, user experience, design issues, as well as concerns on the success of businesses, management, and also organizations, has been accepted to some extent by practitioners [2]. Since user interacts with information, technology and task from various contexts [2], each design of software development must consider user involvement to ensure user satisfaction of the product.…”
Section: A User Involvement and Hcimentioning
confidence: 99%
“…Current SDLC which focuses on functionality is different from the proposed HCSDLC [2] in a number of respects as shown in Figure 1. Several studies by Hoffer et al [1] have revealed that among the many systems development approaches, the SDLC model is a commonly accepted modern structured approach for describing the complex processes and issues in system development.…”
Section: B Comparison Between Current Sdlc and Proposed Hcsdlcmentioning
confidence: 99%
See 2 more Smart Citations
“…HCI includes all aspects of the system that impact its users or other stakeholders. Although the user interface is one of the most noticeable components of the HCI and is key to the systems eventual acceptance, it is not the only part of the HCI development (Zhang et al, 2005).…”
Section: Preliminary Designmentioning
confidence: 99%